Effects of anterior tooth crown inclination on occlusal relationship—A study in three-dimensional reconstruction. (October 2018) - Feng, Feng; Liu, Yifan; Chi, Jingwen; Wang, Yuqiao; Xing, Bin; Wang, Yucheng; Liu, Wen
Highlights: We align the tooth and change the angles or the position of the tooth in the three dimension space. The incisor crown inclination has influence on the establishment of occlusal relationships. The bigger difference upper and lower incisor crown inclination has, the more deviations from the normal occlusal relationship exist. The ideal occlusal relationship depended on both the basal bone's position and the right central incisor crown inclination. Abstract: Objective: This study aims to analyze the relationship between the central incisor crown inclination and occlusal relationship via three-dimensional study. Methods: Ten Chinese volunteers with normal occlusion were selected from physical examination of college students. Lateral cephalograms and CT scans were taken, and the CT data were imported into Simplant pro 11.04 to reconstruct three-dimensional model. In the three-dimensional model, every tooth was separated independently. The upper and lower central incisors were moved labial inclination(up) or lingual inclination(down) and then the upper and lower tooth were aligned based on the central incisor's position according to the principles of Andrew's six keys. Four groups were set up with different changes of central incisors. The upper and the lower arch were aligned again based on the moved central incisors. After every motion, the mesio-distal distances of upper and lower canines and first molars were recorded. All data were analyzed using t -test via SPSS19.0, and the significance level was set at 5%. Results: The results showed that the mesio-distal distances of occlusal relationship were different from normal occlusal relations, when either upper incisor crown inclination or lower incisor crown inclination was changed, and both upper and lower incisor crown inclination were moved in same or opposite direction. According to the statistical analysis, there was no significant difference when the changes of U1-L1 were no more than 10° (P > 0.05). But there was statistically significant difference (P < 0.05) when changes of U1-L1 were more than 20°. Conclusions: The incisor crown inclination has influence on the establishment of occlusal relationships. The bigger difference upper and lower incisor crown inclination has, the more deviations from the normal occlusal relationship exist.